Correction to: Post-transplant inflow modulation for early allograft dysfunction after living donor liver transplantation - Mohamed Elshawy; Takeo Toshima; Yoshiki Asayama; Yuichiro Kubo; Shinichiro Ikeda; Toru Ikegami; Shingo Arakaki; Tomoharu Yoshizumi; Masaki Mori (Surgical Case Reports, 2020)
An amendment to this paper has been published and can be accessed via the original article.